PENGARUH PENGGUNAAN GAME ONLINE MOBILE LEGEND TERHADAP PERILAKU KOMUNIKASI SISWA SMA NEGERI 1 KENDARI - Prasetya, Yoga Yudha; La Tarifu, La Tarifu; La Iba, La Iba (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2020)
ABSTRACTThis study aims to determine and analyze the Effect of Online Game Mobile Legend on Communication Behavior of Students SMA Negeri 1 Kendari. This research is a quantitative study using primary data obtained from questionnaires and measured using a Likert scale. Data were analyzed using simple regression analysis. The population of this research is the XI grade students of SMA Negeri 1 Kendari who have used legend mobile online games with a total of 318 students in which only 14% or 45 students were sampled for this study. The results of this study indicate that the online game mobile legend has a positive effect on communication behavior.Â Key Words : Online Game; Mobile Legend;Communication Behavior